Detailed chemical composition of classical Cepheids in the LMC cluster NGC 1866 and in the field of the SMC - Lemasle, Bertrand; Grebel, Eva K. (Astronomy and astrophysics, 2017)
Cepheids are excellent tracers of young stellar populations. They play a crucial role in astrophysics as standard candles. The chemistry of classical Cepheids in the Milky Way is now quite well-known, however despite a much larger sample, the chemical composition of Magellanic Cepheids has been only scarcely investigated.Aims. For the first time, we study the chemical composition of several Cepheids located in the same populous cluster: NGC 1866, in the Large Magellanic Cloud (LMC). To also investigate the chemical composition of Cepheids at lower metallicity, we look at four targets located in the Small Magellanic Cloud (SMC). Our sample allows us to increase the number of Cepheids with known metallicities in the LMC/SMC by 20%/25% and the number of Cepheids with detailed chemical composition in the LMC/SMC by 46%/50%.Methods. We use canonical spectroscopic analysis to determine the chemical composition of Cepheids and provide abundances for a good number of α, iron-peak, and neutron-capture elements.Results. We find that six Cepheids in the LMC cluster NGC 1866 have a very homogeneous chemical composition, also consistent with red giant branch (RGB) stars in the cluster. Period-age relations that include no or average rotation indicate that all the Cepheids in NGC 1866 have a similar age and therefore belong to the same stellar population. Our results are in good agreement with theoretical models accounting for luminosity and radial velocity variations. Using distances based on period-luminosity relations in the near- or mid-infrared, we investigate for the first time the metallicity distribution of the young population in the SMC in the depth direction. Preliminary results show no metallicity gradient along the SMC main body, but our sample is small and does not contain Cepheids in the inner few degrees of the SMC.